2018
DOI: 10.4236/fns.2018.97065
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional Composition of Bird Egg Varieties Found in Southern Nigeria: A Preliminary Study

Abstract: This study was aimed at comparing nutrient composition of some bird eggs in their raw and boiled forms. The different varieties were exotic chicken, local chicken, turkey, quail and guinea fowl eggs. The eggs were shelled and their contents (boiled and raw) lyophilized. Standard AOAC methods were used for determination of proximate, mineral and vitamin compositions. Results showed the boiled eggs having higher nutrient concentrations than the raw eggs across all species. Guinea fowl egg had significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Guinea fowl yolks presented significantly greater (p < 0.001) βcarotene concentrations, approximately 6.75 and 6.94 times greater than those of chicken and quail egg yolks, respectively. These findings corroborated previous works by Onyenweaku et al (2018) who also reported higher vitamin A levels in guinea fowl yolks than in chicken, quail, or turkey yolks. Environmental factors such as feed materials and weather conditions likely contributed to this variation in β-carotene content (Minh et al, 2006;Franco et al, 2020;Goto et al, 2022).…”
Section: β-Carotene Contentsupporting
confidence: 93%
“…Guinea fowl yolks presented significantly greater (p < 0.001) βcarotene concentrations, approximately 6.75 and 6.94 times greater than those of chicken and quail egg yolks, respectively. These findings corroborated previous works by Onyenweaku et al (2018) who also reported higher vitamin A levels in guinea fowl yolks than in chicken, quail, or turkey yolks. Environmental factors such as feed materials and weather conditions likely contributed to this variation in β-carotene content (Minh et al, 2006;Franco et al, 2020;Goto et al, 2022).…”
Section: β-Carotene Contentsupporting
confidence: 93%
“…The lowest Ca was 160.7 µg g -1 and the highest 1810.0 µg g -1 in egg yolk samples. Our measurements for Ca levels in turkey egg yolks and albumens were higher than those reported by Onyenweaku et al (2018). Calcium is a structural material in the yolk that makes the granular structure of the egg yolk compact insufficiently hydrated and poorly accessible to enzymes and provides effective protection against heat gelation and thermal denaturation (Anton, 2013).…”
Section: Discussionmentioning
confidence: 50%
“…It is a ground feeding bird, characterized by a very wide crown, filled with grey-blue bare skin topped by a prominent horn coloured bony casque (helmet) in red brown colour, a feature which is unique in the guinea fowl [45]. The commercial popularity of the Guinea fowl is on the increase; they are used as ornamental birds [26], pest control in crop farms [36], and dietary source of high protein [26,27]. Studies have also shown that the guinea fowl is relatively more resistant to endemic poultry diseases than the domestic fowl [17,35].…”
Section: Introductionmentioning
confidence: 99%